DETERMINAN FOREIGN DIRECT INVESTMENT DI INDONESIA: PENDEKATAN ARDL PERIODE 1981–2018 - Rofiqotul Qudsiah; Fatah Abdul Jalil (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
Foreign Direct Investment (FDI) refers to capital investment activities undertaken by foreign individuals or legal entities with the intention of conducting business operations in a host country. This study aims to analyze the effects of the exchange rate (IDR/USD), imports, GDP per capita, inflation, and infrastructure on FDI in Indonesia. A quantitative approach was employed using 38 years of time-series data covering the period from 1981 to 2018. The analytical method applied was the Autoregressive Distributed Lag (ARDL) model, supported by EViews 9 software. The results indicate that the exchange rate has a negative and significant effect on FDI in both the short and long run. Imports exert a positive and significant influence on FDI across both time horizons. GDP per capita also shows a positive and significant impact on FDI in the short and long run. In contrast, inflation has a negative and significant effect on FDI over both periods. Additionally, infrastructure demonstrates a positive and significant influence on FDI in both the short and long term. These findings highlight the importance of macroeconomic stability and strong real-sector fundamentals in attracting foreign investment to Indonesia.